Tactics of Two-Stage IOL Implantation in Difficult Refractive Cases - A. A. Kasyanov (Oftalʹmologiâ)
In a number of complex refractive cases, the achievement of an accurate refractive result cannot be guaranteed. Simultaneous implantation of a toric or multifocal IOL for the correction of complex ametropias may be accompanied by a significant deviation from the target refraction. The tactics of two-stage implantation with the usage of an additional Sulcoflex IOL for the final correction of astigmatism and possible residual spherical ametropia allows achieving emmetropia. In our study, this method was used in 15 patients with difficult refractive cases. Toric, multifocal, and multifocal toric Sulcoflex IOL were used. Implantation of all Sulcoflex modifications was performed through a 2.4 mm temporal incision using wound assisted technology. In cases of high degree hypermetropia, preventive iridectomy was performed using a 23G vitrectome. The target refraction was achieved in the entire observation group. In the postoperative period, no significant level of ophthalmic hypertension was registered. No cases of introlens opacification, iridocyclitis, or rotational instability were registered either.The method of two-stage IOL implantation allows achieving the target refraction in difficult refractive situations with almost guaranteed accuracy. The calculation method provides good predictability of the refractive result. This technology significantly expands the indications for intraocular correction using toric and multifocal IOL, as well as the limits of correction of high degree astigmatism. Our Sulcoflex IOL implantation experience has shown their high efficiency and safety.